Benjamin, A Student’s Guide To History - Nance, Star (Teaching History: A Journal of Methods, 2008)
Jules Benjamin articulately provides a history student with a new best friend. A Student’s Guide to History is a nonthreatening, interesting, and useful guide for students to become successful scholars of history. His "cut to the chase" writing style organizes topics in a concise and logical manner, giving examples to elaborate on the topics presented. The chapters are appropriately designed to follow a history course from the beginning of a semester to test taking, formal research, and research paper composition